Speed-up techniques for solving large-scale biobjective TSP - Lust, T.; Jaszkiewicz, A. (Computers & operations research, 2010)
In this paper, we present the Two-Phase Pareto Local Search ( 2PPLS) method with speed-up techniques for the heuristic resolution of the biobjective traveling salesman problem. The 2PPLS method is a state-of-the-art method for this problem. However, because of its running time that strongly grows with the instances size, the method can be hardly applied to instances with more than 200 cities. We thus adapt some speed-up techniques used in single-objective optimization to the biobjective case. The proposed method is able to solve instances with up to 1000 cities in a reasonable time with no, or very small, reduction of the quality of the generated approximations.